2017
DOI: 10.1371/journal.pone.0173260
|View full text |Cite
|
Sign up to set email alerts
|

ITC-derived binding affinity may be biased due to titrant (nano)-aggregation. Binding of halogenated benzotriazoles to the catalytic domain of human protein kinase CK2

Abstract: The binding of four bromobenzotriazoles to the catalytic subunit of human protein kinase CK2 was assessed by two complementary methods: Microscale Thermophoresis (MST) and Isothermal Titration Calorimetry (ITC). New algorithm proposed for the global analysis of MST pseudo-titration data enabled reliable determination of binding affinities for two distinct sites, a relatively strong one with the Kd of the order of 100 nM and a substantially weaker one (Kd > 1 μM). The affinities for the strong binding site dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
4
38
2
Order By: Relevance
“…Below the intersection, point absorbance increased linearly with increasing concentration obeying the Lambert-Beer law. Above this point, deviation from the linearity upon increasing concentration indicated aggregation phenomenon (Winiewska et al, 2017). This might be due to the hurdle that is faced by UV-Vis radiations to pass through the inner core of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Below the intersection, point absorbance increased linearly with increasing concentration obeying the Lambert-Beer law. Above this point, deviation from the linearity upon increasing concentration indicated aggregation phenomenon (Winiewska et al, 2017). This might be due to the hurdle that is faced by UV-Vis radiations to pass through the inner core of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Monomodal distribution of the aggregates was observed for each concentration showing the uniformity of the aggregate formation. Larger size aggregates showed less relaxation time due to their decreased diffusion velocity as compared to smaller size aggregates, obeying Stokes-Einstein equation, which shows inverse relation between hydrodynamic radius and diffusion velocity (Winiewska et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In this substantial approach, MST and SPR were used for the interaction study. On the other hand, the small molecules inhibitory effect was investigated extensively via MST [59][60][61][62][63][64]. Where, Shang et al [60] successfully investigated small molecule as inhibitor G-protein-coupled Rho guanine nucleotide exchange factors.…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%
“…Previously, it has been shown that enzymatically acetylated MtrA is a better phosphoacceptor from MtrB ( Singh et al, 2019 ). To determine the binding affinity of AcP to the MtrA protein, we generated a fluorescently (RFP) tagged MtrA protein for MST analysis, similar to what has been reported previously ( Winiewska et al, 2017 ; Singh et al, 2019 ). The fluorescently tagged protein was first confirmed to be active in the phosphotransfer assay from MtrB ( Supplementary Figures 2A,B ).…”
Section: Resultsmentioning
confidence: 99%